1992
DOI: 10.1007/bf01371232
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of fibronectin as a tool for the age determination of human skin wounds

Abstract: Summary:We analyzed the distribution of fibronectin in routinely embedded tissue specimens from 53 skin wounds and 6 postmortem wounds. In postmortem wounds a faint but focal positive staining was exclusively found at the margin of the specimens which dit not extend into the adjacent stroma. Vital wounds were classified into 3 groups. The first comprising lesions with wound ages ranging from a few seconds to 30min, the second comprising those with wound ages upt to 3 weeks, and the third group with lesions mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
1
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 32 publications
(39 reference statements)
9
53
1
1
Order By: Relevance
“…1). However, in 6 of these cases, a distinct reaction for fibronectin in the form of strongly reacting strings with a beginning formation of network-like structures was demonstrable which indicates a vital reaction as previously described [3]. In some cases a band-shaped weak staining for fibronectin also occurred in marginal regions but this reaction was clearly distinguishable from vital fibronectin staining and only restricted to the outer areas of the margins.…”
Section: Fibronectinsupporting
confidence: 68%
See 3 more Smart Citations
“…1). However, in 6 of these cases, a distinct reaction for fibronectin in the form of strongly reacting strings with a beginning formation of network-like structures was demonstrable which indicates a vital reaction as previously described [3]. In some cases a band-shaped weak staining for fibronectin also occurred in marginal regions but this reaction was clearly distinguishable from vital fibronectin staining and only restricted to the outer areas of the margins.…”
Section: Fibronectinsupporting
confidence: 68%
“…Fechner et al [8] showed that the immunohistochemical localization of fibronectin was suitable for indicating vitality of skeletal muscle damage. The advantage of the detection of this glycoprotein as a vital sign in human skin wounds with a survival time of at least a few minutes was demonstrated by our own previous results [3].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Immunohistochemistry is not only useful for the detection of early changes during wound repair [3], but also provides significant information on the time-dependent appearance of various extracellular matrix components during the proliferative and reparative phases of wound healing.…”
Section: Introductionmentioning
confidence: 99%